LEGAL FOUNDATIONS FOR PROTECTING WOMEN FROM PRESSURE AND VIOLENCE - Ra’no Parpievna, Rustamova (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2025)
Objective: This study aims to critically examine international treaties—specifically CEDAW and the UN Declaration on the Elimination of Violence Against Women—and Uzbekistan’s national legislation to assess their effectiveness in protecting women’s rights against violence and pressure. Method: A qualitative approach was employed, involving an in-depth analysis of international legal frameworks, national laws, and sociocultural contexts that influence enforcement practices. Results: The findings reveal that despite the existence of comprehensive global and domestic legal instruments, significant challenges persist due to cultural barriers, insufficient enforcement mechanisms, and limited access to victim support services. National initiatives, including Uzbekistan’s Law on Domestic Violence, mark progress but require stronger implementation efforts and broader societal transformation. Novelty: This research integrates legal and sociocultural analysis, offering a dual perspective that highlights not only the legal deficiencies but also the underlying structural and societal obstacles to effective protection, thus contributing original insights to the field of human rights and gender-based violence prevention.